MasterFile Core SER-01 - Roisenberg, Henrique Berger; Savian, Jairo Francisco; de Mello, Raquel Gewehr; Leandro, Carolina Gonçalves; Pontel, Caroline Azzolini; Frigo, Everton; Fauth, Gerson; Santos, Alessandra; Baecker-Fauth, Simone; Bruno, Mauro Daniel R.; Guerra, Rodrigo; Krahl, Guilherme; et al. (Zenodo, 2022)
This Master File presents the paleomagnetic data for Core SER-01 from Sergipe-Alagoas Basin, NE Brazil. This data was published in the research article " Paleomagnetic results of Early Cretaceous sediments from South Atlantic Ocean: Implications for paleosecular variation and relative paleointensity".